China – The New Developmental State? : An Empirical Analysis of the Automotive Industry (2018)
The central focus of this analysis is whether the economic growth of China can be attributed to an emulation of the development models of Japan, South Korea, and Taiwan. Based on the developmental state theory, an East Asian developmental state model is set up as a benchmark. The thesis uses an empirical analysis of the auto industry to highlight the performance outcome of China’s development strategy. The author confirms that China has evolved into a developmental state similar in its core characteristics to the three leading East Asian states. The model of development in China, however, is an innovative combination of factors from the developmental states, the legacies of the past command economy as well as of the adopted market economy mechanism including international capital flows.